Karakteristik Sinkop Tokoh dengan Autism Spectrum Disorder dalam Film Miracle In Cell No. 7 - Moh. Rofi Al Muhasibi; Mariam Ulfa; Ria Kristia Fatmasari (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to describe the forms, patterns, and factors of syncope in the speech of Autism Spectrum Disorder (ASD) characters in the film Miracle in Cell No. 7. This research uses a qualitative descriptive approach with data sources in the form of dialogues of the character Dodo Rozak which contain symptoms of phoneme omission in the middle position of words. Data were collected through the listening method with the advance collection technique, namely the note-taking technique, and supported by linguistic documentation. Analysis was carried out using the distribution method with the determinant sorting technique to identify the       1         phonological structure of words experiencing syncope, as well as a comparative method to compare the form of speech with the standard form of Indonesian. The results of the study indicate that the syncope process occurs systematically in the medial position of words, especially in complex syllable structures, as a form of articulatory simplification. This phenomenon is not random, but rather reflects a language production strategy related to the phonological and cognitive aspects of ASD speakers. This study confirms that syncope in the speech of ASD characters can be analyzed linguistically as a structured phonological process and contributes to the study of Indonesian phonology and psycholinguistics.